Taxation and incentives to innovate: A principal-agent approach - Diego d'Andria (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2014)
A principal-agent multitasking model is used to explore the effects of different tax schemes on innovation in a pure knowledge economy. Corporate taxes and labor income taxes can affect both the firm owner's and the employee's incentives to commit to innovative tasks, when the former compensates the latter (a manager, technical or R&D employee) by means of variable pay tied to measures of the company's success. Results point to a complementary role between 'patent box' tax incentives and reductions in the tax rate levied on profit sharing schemes. This complementarity holds, albeit with different relative importance for the two tax incentives, also with non-deductible labor costs, with a stochastic innovation value coupled with a risk-averse agent, and with multiple principals competing for talented agents.
Keywords: H2; O31; J33; 330; incentives to innovate; multitasking models; patent box; principal-agent models; profit sharing schemes; tax incentives for R&D